Catalytic enantio- and diastereoselective Mannich reaction of α-substituted isocyanoacetates and ketimines. Issue 70 (8th August 2016) - de la Campa, Raquel; Gammack Yamagata, Adam D.; Ortín, Irene; Franchino, Allegra; Thompson, Amber L.; Odell, Barbara; Dixon, Darren J.
Abstract : The highly diastereo- and enantioselective Mannich reaction/cyclisation of α-substituted isocyanoacetates and ketimines catalysed by silver acetate and a cinchona-derived amino phosphine is reported. Abstract : The highly diastereo- and enantioselective Mannich addition/cyclisation reaction of α-substituted isocyanoacetate ester pronucleophiles and (hetero)aryl and alkyl methyl ketone-derived ketimines using a silver acetate and a cinchona-derived amino phosphine binary catalyst system is reported.